Peran Pemerintah Kelurahan dalam Prencanaan Pembangunan Infrastruktur Jalan di Kelurahan Amal Bakti Kecamatan Kateman Kabupaten Indragiri Hilir - Rianto, Rianto; Suherry, Suherry; Dwiniati, Dwiniati; Riska Ayu, Agustina (Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
Amal Bakti Village is one of the villages located on the Guntung River, Kateman District. The average area in Amal Bakti Village has problems with infrastructure development, especially connecting roads, as access for the community. The road in Amal Bakti Village is still dirt and only partially paved, making it difficult to travel when it rains heavily. The purpose of this study is to find out the role of the Village Government in Planning for Infrastructure Development in Amal Bakti Village. In this study the theory used according to Siagian (2000: 142-150). In this study, a sample of 5 people was taken. The data analysis technique used in this research is descriptive qualitative. Based on the results of the study, it can be concluded that the role of the Village Government in Road Infrastructure Development Planning (Study in Amal Bakti Village, Kateman District, Indragiri Hilir Regency) is not optimal, this is because there are still many damaged infrastructure developments, the government conducts musrenbang in determining development priorities, but some developments that occur outside of deliberation, then often encounter obstacles such as lack of program socialization or otherwise the village community does not respond or participate in programs promoted by the government. The suggestions that can be conveyed are that the Government must be able to see priority road construction, including those that are frequently passed and become important access for the community. There must be deliberation by involving the community to hear suggestions and input so that development is more targeted.